An open-aperture partially-evacuated receiver for more uniform reflected solar flux in circular-trough reflectors: Comparative performance in air heating applications. (October 2021) - Madadi Avargani, Vahid; Norton, Brian; Rahimi, Amir
Abstract: Trough reflectors can produce a reflected solar flux density that is highly concentrated in specific regions of the receiver surface causing higher thermal losses as well as increasing the likelihood of mechanical damage to the receiver. Time-dependent three-dimensional computational fluid dynamics models were developed and used to compare optical and thermal performances of unglazed tubular, evacuated tubular, and open-aperture evacuated receivers for air heating applications. An evacuated partial-annulus receiver with a non-evacuated open-aperture in the high-density solar flux area produced a more uniform concentrated solar flux distribution. With an open aperture to high-density solar flux, an open-aperture evacuated receiver (i) avoids a dense distribution of reflected solar flux in a specific area of an absorber surface thereby contributing to realizing long-term mechanical integrity, (ii) gives a greater optical performance in all types of trough reflector than an evacuated tubular receiver, (iii) tolerates optical mispositioning and (iv) is particularly suited for use with circular trough reflectors.